The origins of the RAG genes – from transposition to V(D)J recombination - Fugmann, Sebastian D. (2009)
The Recombination Activating Genes 1 and 2 (Rag1 and Rag2) encode the key enzyme that is required for the generation of the highly diversified antigen receptor repertoire central to adaptive immunity. The longstanding model proposed that this gene pair was acquired by horizontal gene transfer to explain its abrupt appearance in the vertebrate lineage. The analyses of the enormous amount of sequence data created by many genome sequencing projects now provides the basis for a more refined model as to how this unique gene pair evolved from a selfish DNA transposon into a sophisticated DNA recombinase essential for immunity.